High-responsivity two-dimensional p-PbI2/n-WS2 vertical heterostructure photodetectors enhanced by photogating effect. Issue 7 (23rd April 2019) - Qi, Zhaoyang; Yang, Tiefeng; Li, Dong; Li, Honglai; Wang, Xiao; Zhang, Xuehong; Li, Fang; Zheng, Weihao; Fan, Peng; Zhuang, Xiujuan; Pan, Anlian
Abstract : High-performance vapor-grown PbI2 /WS2 heterostructure photodetectors enhanced by the photogating effect. Abstract : Two-dimensional (2D) vertical p–n heterostructure photodetectors are significant building blocks in nanoscale integrated optoelectronics. However, the unsatisfactory photosensing performance combined with a complicated fabrication process still remains a challenge. In this work, the fabrication of high-performance vertical photodetectors based on vapor-grown p-PbI2 /n-WS2 heterostructures has been reported, where WS2 serves as the photogate to modulate the channel current. Due to the photogating effect in heterostructures, the recombination of photoexcited electron–hole pairs is effectively suppressed, leading to high photoresponsivity up to 5.57 × 10 2 A W −1, which represents the highest value among any other reported vapor-grown vertical p–n heterostructures. Moreover, the photoresponsivity is highly tunable through the gate voltage bias, and it can be further improved to 7.1 × 10 4 A W −1 by applying a negative gate voltage bias of −60 V. The excellent photosensing properties of the PbI2 /WS2 heterostructures combined with the facile synthesis method reveal the promising potential in developing high-performance 2D optoelectronic devices.